Aetiological profile of acute encephalitis syndrome in Assam, India, during a 4‐year period from 2019 to 2022 - Sonowal, Dharitree; Sharma, Ajanta; Sarmah, Kimmi; Upadhaya, Deepak; Kumar, Sachin; Kaur, Harpreet (APMIS : acta pathologica, microbiologica et immunologica Scandinavica, 2024)
Acute encephalitis syndrome (AES) is a major public health concern in India as the aetiology remains unknown in the majority of cases with the current testing algorithm. We aimed to study the incidence of Japanese encephalitis (JE) and determine the aetiology of non‐JE AES cases to develop an evidence‐based testing algorithm. Cerebrospinal fluid (CSF) samples were tested for Japanese encephalitis virus by ELISA and polymerase chain reaction (PCR). Multiplex real‐time PCR was done for Dengue, Chikungunya, West Nile, Zika, Enterovirus, Epstein Barr Virus, Herpes Simplex Virus, Adenovirus, Cytomegalovirus, Herpesvirus 6, Parechovirus, Parvovirus B19, Varicella Zoster Virus, Scrub typhus, Rickettsia species, Leptospira, Salmonella species, Streptococcus pneumoniae, Haemophilus influenzae, Neisseria meningitidis, Plasmodium species and by ELISA for Mumps and Measles virus. Of the 3173 CSF samples, 461 (14.5%) were positive for JE. Of the 334 non‐JE AES cases, 66.2% viz. Scrub typhus (25.7%), Mumps (19.5%), Measles (4.2%), Parvovirus B19 (3.9%) Plasmodium (2.7%), HSV 1 and 2 (2.4%), EBV and Streptococcus pneumoniae (2.1% each), Salmonella and HHV 6 (1.2% each) were predominant. Hence, an improved surveillance system and our suggested expanded testing algorithm can improve the diagnosis of potentially treatable infectious agents of AES in India.